Study of the Activity of Ni/H5-NZA Catalyst and Co(II)/H5NZA to Catalytic Cracking Methyl Ester Jatropha - Novita Andarini (Jurnal ILMU DASAR, 2011)
The catalytic activity of H5NZA, Ni/H5NZA and Co/H5NZA converting methyl ester jatropha have been studied. The reaction was proceeded in flow fixed bed reactor that operated at the temperature of 450oC for 60 minutes using butanol as the catching-feed. The catalysts were prepared by acidifying of natural zeolite using HF 1%, HCl 6 M and NH4Cl 0.1 M), it was then hydrothermally treated and calcinated with nitrogen. Finally, it is oxidized and impregnated by ion nickel and cobalt (2% w/w). Meanwhile, the methyl ester jatropha as feed stocks was prepared by reacting a jatropha oil with sodium methoxy. The catalytic process was done by placing a catalyst on the flow fixed bed reactor at the temperature of 450oC and flowing a methyl ester and butanol to the reactor for 60 minutes with a fixed flow rate. A liquid fraction have been produced and were then characterized using GC. The maximum percentage conversion of methyl ester was found to be 94.6891% using catalyst of zeolite acid H5NZA which were indicated by a reduction signal of the original methyl ester. The selectivity of this catalyst was performed by the specific product on the retention time of <2.5 minutes. The modified catalysts which were impregnated by the ion Ni and Co shown their selectivity on range of retention time of 2.5-5.0 and 5.0-10 minutes respectively.